Social processes and communal tension: a case study of Vadodara city - Rajaram, N. (New Delhi, 2006)
This study was conducted during 2000-01 and the report submitted in December 2001. The focus of this study was why Baroda did not have riots in December 1992, and thereafter, when in the aftermath of the demolition of the Babri Masjid the country was engulfed in a frenzy of rioting. A city which was notorious for communal riots in the eighties, was - for want of a better phrase-riot-free. This spell of freedom from riots, interestingly, continued throughout the nineties. So when the study was conducted during 2000-01, it had as its focus the situation of 1990s; and the style of the report has that flavour. Subsequent to the submission of the report in late 2001, the infamous 2002 riots occurred - starting in late February and intermittently occurring for a period of four months. Gujarat and Vadodara were very deeply affected by these occurrences.
Keywords: Communal violence-Vadodara( Gujarat)